Gender Differences in Clinical, Angiographic and Procedural Profiles between Young Patients with Acute Coronary Syndrome undergoing Percutaneous Coronary Intervention (Cardiovascular Journal, 2018)
Background: Acute coronary syndrome (ACS) is increasingly prevalent among young patients, particularly in South Asia, where young patients are known to present with multiple risk factors and gender-based differences in angiographic profiles. This study aimed to compare gender differences in clinical, angiographic and procedural profiles between young patients with ACS undergoing percutaneous coronary intervention (PCI).Methods: This prospective observational study was done at the National Institute of Cardiovascular Diseases (NICVD) from April 2016 to March 2017. 190 young patients with ACS undergoing PCI were included. Clinical, angiographic and procedural variables were compared and statistically analyzed.Results: The mean age of young females and males was 43.8±6.9 years and 40.1±4.3 years respectively (p